2016
DOI: 10.4269/ajtmh.15-0677
|View full text |Cite
|
Sign up to set email alerts
|

Herd Protection from Drinking Water, Sanitation, and Hygiene Interventions

Abstract: Herd immunity arises when a communicable disease is less able to propagate because a substantial portion of the population is immune. Nonimmunizing interventions, such as insecticide-treated bednets and deworming drugs, have shown similar herd-protective effects. Less is known about the herd protection from drinking water, sanitation, and hand hygiene (WASH) interventions. We first constructed a transmission model to illustrate mechanisms through which different WASH interventions may provide herd protection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 58 publications
3
68
1
Order By: Relevance
“…Diarrheal disease is transmitted through interactions between agents and the environment (Figure ). In our ABM, the transmission can be described with two pathways, which is similar to those in the model of Fuller and Eisenberg . First, infectious people shed pathogens into their household.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diarrheal disease is transmitted through interactions between agents and the environment (Figure ). In our ABM, the transmission can be described with two pathways, which is similar to those in the model of Fuller and Eisenberg . First, infectious people shed pathogens into their household.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of Fuller and Eisenberg , we developed an agent‐based model of diarrheal disease transmission in a community using Anylogic 7.3.5, a common agent‐based simulation platform. Our ABM simulates the diarrheal disease transmission with approximately 500 individuals within 100 households.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One observational study from national survey data in India found that community coverage was related to diarrhea [115], but another observational study found no effect of community coverage on diarrhea in Mali [9]. Additional theoretical model analysis has suggested that all benefits from sanitation interventions come from the indirect effects due to community coverage [116]. There is not enough evidence to know if these latrine interventions could have had a stronger effect at higher coverage, but it is possible that not approaching herd protection was a factor in the observed results of the WASH-Benefits Kenya and SHINE trials.…”
Section: Intervention Coveragementioning
confidence: 99%
“…Fuller & Eisenberg [50] stated that understanding the role of herd protection from drinking water, sanitation, and hand hygiene (WASH) interventions can help inform coverage targets and strategies that indirectly protect those that are unable to be reached by WASH campaigns. Abalo et al [51] prominent people were invited to intermittently grace the National Sanitation Day (NSD) exercise, their invitations should be to empower the local people toesteem the importance of the programme by making it their own rather than depending on their presence to increase patronage.…”
Section: Social Campaignmentioning
confidence: 99%